Ecological Crime as An International Crime: A Study on The Prospects of Implementing the Principle of Ecocide Within Indonesian Criminal Law - Lestari, Putu Ulandari Sri; Negara, I Putu Endra Wijaya (TATOHI: Jurnal Ilmu Hukum, 2026)
Introduction: Environmental damage in Indonesia has reached alarming levels, with ecological, social, economic, and transboundary impacts. The existing environmental criminal law system, particularly through the Environmental Management Act and other sectoral regulations, still faces fundamental weaknesses in the form of disharmonious regulations, weak law enforcement, and limited implementation of corporate criminal liability. This situation indicates a normative and practical gap that prevents ecological crimes from being treated as extraordinary crimes. Meanwhile, international developments through the concept of ecocide emphasize the urgency of placing massive environmental destruction on a par with genocide, crimes against humanity, war crimes, and aggression. Purposes of the Research: The purpose of this study is to analyze the normative and practical gaps in Indonesian environmental criminal law on the concept of ecocide, as well as provide specific recommendations for regulatory harmonization and strengthening the capacity of law enforcement to respond to these challenges. Methods of the Research: This study uses a normative juridical method with conceptual, legislative, and comparative legal approaches. Findings of the Research: The results show that the application of ecocide principles in Indonesia faces challenges, such as the lack of an official definition, overlapping regulations, weak coordination between institutions, and the low technical capacity of law enforcement officials. Nevertheless, the opportunity for ecocide recognition is wide open, supported by international precedent, academic pressure, and the urgency of large-scale environmental cases in Indonesia. Therefore, environmental criminal law reform is crucial to integrate ecocide into national law, in order to strengthen ecological protection and affirm Indonesia's commitment to sustainable development and global environmental diplomacy.